Closely Related Poleroviruses Depend on Distinct Translation Initiation Factors to Infect Arabidopsis thaliana - C. Reinbold; S. Lacombe; V. Ziegler-Graff; D. Scheidecker; L. Wiss; M. Beuve; C. Caranta; V. Brault (Molecular Plant-Microbe Interactions, 2013)
In addition to being essential for translation of eukaryotic mRNA, translation initiation factors are also key components of plant–virus interactions. In order to address the involvement of these factors in the infectious cycle of poleroviruses (aphid-transmitted, phloem-limited viruses), the accumulation of three poleroviruses was followed in Arabidopsis thaliana mutant lines impaired in the synthesis of translation initiation factors in the eIF4E and eIF4G families. We found that efficient accumulation of Turnip yellows virus (TuYV) in A. thaliana relies on the presence of eIF (iso)4G1, whereas Beet mild yellowing virus (BMYV) and Beet western yellows virus-USA (BWYV-USA) rely, instead, on eIF4E1. A role for these factors in the infectious processes of TuYV and BMYV was confirmed by direct interaction in yeast between these specific factors and the 5′ viral genome-linked protein of the related virus. Although the underlying molecular mechanism is still unknown, this study reveals a totally unforeseen situation in which closely related viruses belonging to the same genus use different translation initiation factors for efficient infection of A. thaliana.